Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please help me to find a closed form for the sum $$\sum_{n=1}^\infty\frac{(-1)^n n^4 H_n}{2^n},$$ where $H_n$ are harmonic numbers: $$H_n=\sum_{k=1}^n\frac{1}{k}=\frac{\Gamma'(n+1)}{n!}+\gamma.$$

share|improve this question
11  
Is it possible to generalize it to n^a instead of n^4? math.stackexchange.com/questions/385094/… –  Piotr Shatalin May 8 '13 at 2:35

3 Answers 3

up vote 18 down vote accepted

$$\sum_{n=1}^\infty\frac{(-1)^n n^4 H_n}{2^n}=\frac{28}{243}+\frac{10}{81} \log \left(\frac{2}{3}\right).$$

Hint: Change the order of summation: $$\sum_{n=1}^\infty\frac{(-1)^n n^4 H_n}{2^n}=\sum_{n=1}^\infty\sum_{k=1}^n\frac{(-1)^n n^4}{2^n k}=\sum_{k=1}^\infty\sum_{n=k}^\infty\frac{(-1)^n n^4}{2^n k}.$$

share|improve this answer
1  
How is this a hint? –  Did Aug 26 '13 at 21:54

A related problem. Here is another approach. Recalling the generating function of the harmonic numbers

$$ \sum_{n=1}^{\infty} H_n x^n = \frac{\ln(1-x)}{x-1} \implies (xD)^4\sum_{n=1}^{\infty} H_n x^n=(xD)^4 \frac{\ln(1-x)}{x-1}, $$

$$ \implies \sum_{n=1}^{\infty} H_n n^4 x^n = {\frac {x \left( 1+11\,x+11\,{x}^{2}+{x}^{3} \right) \ln \left( 1-x \right) }{ \left( -1+x \right) ^{5}}}+{\frac {x \left( -1-27\,{x}^{2} -18\,x-4\,{x}^{3} \right) }{ \left( -1+x \right) ^{5}}}.$$

Substituting $x=-\frac{1}{2}$ in the above identity gives the desired result

$$ \sum_{n=1}^\infty\frac{(-1)^n n^4 H_n}{2^n}={\frac {28}{243}}-{\frac {10}{81}}\,\ln \left( \frac{3}{2} \right). $$

share|improve this answer
1  
Pretty nifty (+1). –  Ron Gordon Aug 26 '13 at 20:39
    
@RonGordon: Thanks for the comment. –  Mhenni Benghorbal Sep 3 '13 at 17:31
1  
+1. That was the 'natural' way. –  Felix Marin Sep 12 at 18:13
    
@FelixMarin: Thanks for the comment. I really appreciate it. –  Mhenni Benghorbal Sep 12 at 18:24

Hint: Set $f_k=H_k$ and find a function $g_k$ such that $g_{k+1}-g_k=\frac{(-1)^kk^4}{2^k}$ and use summation by parts to get: $$\sum_{k=1}^nf_k(g_{k+1}-g_k)=f_{n+1}g_{n+1}-f_1g_1-\sum_{k=1}^n(f_{k+1}-f_k)g_{k+1}$$ $$\sum_{k=1}^nH_k(\frac{(-1)^kk^4}{2^k})=f_{n+1}g_{n+1}-f_1g_1-\sum_{k=1}^n(\frac{1}{k+1})g_{k+1}$$ Find the limit as $n\rightarrow \infty$. $g_k$ will be a function of the form $(\frac{-1}{2})^kp(k)+C$ for some polynomial $p$ and constant $C$. Thus, I believe the RHS will be a sum of the form: $$\sum_{k=1}^{\infty}[(\frac{-1}{2})^kp(k)+C]\frac{1}{k+1}$$ which will be just tedious to evaluate.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.